Design and simulation voltage dynamic restorer (DVR) - Mohd Norfarhan, Mohd Mustafa (2010)
This thesis describes the problem of voltage sags and swells and its severe impact on non linear loads or sensitive loads. The dynamic voltage restorer (DVR) has become popular as a cost effective solution for the protection of sensitive loads from voltage sags and swells. The control of the compensation voltages in DVR based on dqo algorithm is discussed. It first analyzes the power circuit of a DVR system in order to come up with appropriate control limitations and control targets for the compensation voltage control. Simulation results carried out by Matlab/Simulink verify the performance of the proposed method.